PROTECTING WIVES' RIGHTS: KYAI HUSEIN MUHAMMAD'S REINTERPRETATION OF SEXUAL OBLIGATIONS IN MARRIAGE - Rinangku, Dzatul Kahfi Bagus; Munawaroh, Lathifah (Kafa`ah: Journal of Gender Studies, 2025)
Islamic texts that talk about fulfilling the obligation to serve husbands for wives are often understood biasedly by couples, and even seem to ignore the protection of wives' reproductive rights. Husbands often do not understand the condition of their wives, which often results in unilateral prosecution of rights by arguing that the wife is a sin if she does not serve her husband, under any circumstances. Several existing texts are used to reinforce this attitude. This is different from Kyai Husein Muhammad, who has another opinion, that the wife has the right to refuse sexual relations. Here it appears as if there is a paradox and conflict in the interpretation of religious texts. This article analyzes Kyai Husein Muhammad's perspective in interpreting religious texts with the aim of providing protection for wives' reproductive rights in the family. This article is the result of normative legal using primary data sources with interviews with Kyai Husein Muhammad and primary legal materials: Kyai Husein Muhammad’s books.This article produces several points: first, Kyai Husein Muhammad's istinbāṭ law regarding the reproductive protection rights of wives which focuses on the hadith of the wife's refusal to have sexual relations with her husband, which needs to be underlined, namely do not stop in a statement, and always ask again in the statement, don't easily satisfied with a statement. Second: Kyai Husein Muhammad's current thoughts about wives being allowed to refuse sexual relations are relevant because they offer protection to the wife's rights in marriage.